Hello and Good Morning/Afternoon:
<u>Let's take this problem step-by-step:</u>
<u>First off, let's write the line in point-slope form:</u>
![\rm \hookrightarrow (y-y_0)=m(x-x_0)](https://tex.z-dn.net/?f=%5Crm%20%5Chookrightarrow%20%28y-y_0%29%3Dm%28x-x_0%29)
- (x₀, y₀) any random point on the line
- 'm' is the value of the slope
<u>Let's calculate the slope:</u>
![\rm \hookrightarrow Slope = \frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Crm%20%5Chookrightarrow%20Slope%20%3D%20%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
- (x₁, y₁): any random point on the line ⇒ (-2, -6)
- (x₂,y₂): any random point on the line that is not (x₁, y₁) ⇒ (2, -3)
![\rm \hookrightarrow slope = \frac{-3--6}{2--2} =\frac{3}{4}](https://tex.z-dn.net/?f=%5Crm%20%5Chookrightarrow%20slope%20%3D%20%5Cfrac%7B-3--6%7D%7B2--2%7D%20%3D%5Cfrac%7B3%7D%7B4%7D)
<u>Now that we found the slope, let's put it into the point-slope form</u>
⇒ we need (x₀, y₀) ⇒ let's use (2,-3)
![(y-(-3))=\frac{3}{4} (x-2)\\y+3=\frac{3}{4} (x-2)](https://tex.z-dn.net/?f=%28y-%28-3%29%29%3D%5Cfrac%7B3%7D%7B4%7D%20%28x-2%29%5C%5Cy%2B3%3D%5Cfrac%7B3%7D%7B4%7D%20%28x-2%29)
<u>The equation, however, could also be put into 'slope-intercept form'</u>
⇒ gotten by isolating the 'y' variable to the left
<u>Answer:</u>
or ![y+3=\frac{3}{4} (x-2)](https://tex.z-dn.net/?f=y%2B3%3D%5Cfrac%7B3%7D%7B4%7D%20%28x-2%29)
*<em>Either equations work, put the one that you are the most familiar with</em>
Hope that helps!
#LearnwithBrainly
-2 < -1,5p - 8
-1,5p - 8 > -2
-1,5p > -2 + 8
-1,5p > 6 / : (-1,5)
<u>x</u><u> </u><u><</u><u> </u><u>4</u>
Answer:
the answer is vertices
hope this helps!
Step-by-step explanation:
Product factor is an expression in where you multiply the same value digit many times.
Exponent is the expression in where you convert product factor expression into a shorter expression
For example of product factor:
=> 9 x 9 x 9 x 9 x 9 x 9 x 9 x 9 x 9
As you can see, 9 is multiplied many times, that makes it longer.
Now, let’s make this product factor shorter using exponent.
=> since 9 is multiplied 9 times the exponent expression is:
=> 9 9 in where 9 is the base and the other 9 is called exponent.